2019
DOI: 10.1103/physrevmaterials.3.064409
|View full text |Cite
|
Sign up to set email alerts
|

Lorentz TEM investigation of chiral spin textures and Néel Skyrmions in asymmetric [Pt/(Co/Ni)M/Ir]N multi-layer thin films

Abstract: We examine magnetic domain patterns in symmetric [Co/Ni]M and asymmetric [Pt/(Co/Ni)M /Ir]N multi-layers using Fresnel mode Lorentz transmission electron microscopy (LTEM). In the symmetric multi-layer, where the Dzyaloshinskii-Moriya Interaction is expected to be zero, we observe purely Bloch type domain walls with no preferred chirality. In the asymmetric multi-layers, where significant interfacial DMI is present, we observe domain patterns with chiral Néel domain walls, which evolve into sub-100nm isolated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…An example of such a scenario is illustrated in Figure 3. This behavior is also in line with observed transitions from π-to 2π-VBLs in multilayer films with D < D c as the film thickness decreases [19,20]. Moreover, we anticipate that horizontal Bloch lines would exhibit similarly asymmetric behavior.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…An example of such a scenario is illustrated in Figure 3. This behavior is also in line with observed transitions from π-to 2π-VBLs in multilayer films with D < D c as the film thickness decreases [19,20]. Moreover, we anticipate that horizontal Bloch lines would exhibit similarly asymmetric behavior.…”
supporting
confidence: 88%
“…The above analysis makes a number of reasonable yet noteworthy assumptions about DW switching-in particular, that the process occurs coherently without the formation of vertical or horizontal Bloch lines (VBLs and HBLs, respectively). Li et al found that the presence of VBLs increased with decreasing thickness [19,20]. Moreover, the study in [18] concluded that HBLs mediated switching in the thick films studied; these results have recently been corroborated [21].…”
mentioning
confidence: 79%
“…Contrast can be obtained by tilting the sample, so that a fraction of the out-of-plane magnetic field is projected onto a plane perpendicular to the optical axis of the microscope (Benitez et al, 2015;Pollard et al, 2017). Fresnel defocus images have been used to study Néel-type magnetic skyrmions in a variety of multilayer samples (Pollard et al, 2017;He et al, 2018;McVitie et al, 2018;Fallon et al, 2019;Garlow et al, 2019;Jiang et al, 2019;Li et al, 2019) in the presence of different external stimuli (He et al, 2017;Zhang et al, 2018aZhang et al, , 2018b. However, it is difficult to obtain well-resolved Fresnel defocus images of small Néel-type magnetic skyrmions with high contrast for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The Dzyaloshinskii-Moriya interaction (DMI) found in bulk magnetic non-centrosymmetric crystals 1,2 and at the heavy metal/ferromagnetic interfaces of magnetic multi-layer films 3 has generated considerable interest in magnetic bubbles with inherent topological protection, also known as skyrmions [4][5][6][7][8] . These spin structures have been proposed for a wide range of spintronic applications, including devices for next-generation data storage 9,10 and neuromorphic computing 11,12 as they can be manipulated with remarkable efficiency using magnetic fields and electric currents 13,14 .…”
mentioning
confidence: 99%
“…Additionally, topologically trivial bubbles (Q = 0), also known as type II bubbles, have been observed in the case of weak DMI alongside achiral Bloch bubbles (see Figure 2 schematic). 8 These type II bubbles contain two vertical Bloch lines (with parallel alignment), which are 180 • transitions of the internal magnetization in a Bloch domain wall. It is noteworthy that, because a uniformly magnetized film has Q = 0, there is no required break in topology to annihilate a type 2 bubbles (i.e.…”
mentioning
confidence: 99%